The IMF and the Latin American Debt Crisis : Seven Common Criticisms - Boughton, James (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1994)
The IMF played a key role in developing and implementing the debt strategy throughout the 1980s. That strategy not only overcame the crisis but also produced successful transformationsof several major economiesin Latin America. Nonetheless, the IMF's role has also been criticized on several grounds. This study examines seven such criticisms.